Tom Stoppard’s The Invention of Love: the Invention of Tradition - Kucała, Bożena (American & British Studies Annual, 2010)
The article discusses Stoppard’s play as an instantiation of how literary tradition is invented. By problematising the processes of artistic creation, transmission (especially by means of verbal communication) and interpretation of literature, the play demonstrates that the emergence of tradition is not a matter of natural growth. Based on the biography of A.E. Housman, The Invention of Love presents Housnam’s tentative attempts at identifying himself and, especially, at defining the nature of his commitment to another man. Housman’s self-perception is shaped by his knowledge of literature, and in particular classical culture. It is mainly in the work of ancient poets that the protagonist finds models for his own feelings. In his own poetry, Housman also gives priority to fabulation rather than imitation of reality. It is argued here that both his creative and scholarly work as well as his private life exemplify a variety of the processes by which literary tradition is constructed.